Rove beetle collection (Coleoptera: Staphylinidae: Aleocharinae) in the State Museum of Natural History (Lviv, Ukraine) - Glotov, Serhii V.; Hushtan, Kateryna V.; Rizun, Volodymyr B. (Zootaxa, 2023)
The collection of rove beetles of the subfamily Aleocharinae, stored in the State Museum of Natural History of the National Academy of Sciences of Ukraine (Lviv), has been catalogued. The catalog contains information about 2313 specimens of the collection, which belong to 278 species in 91 genera and 17 tribes. The overwhelming majority of the representatives of the subfamily Aleocharinae represented in the collection were collected on the territory of Ukraine, as well as in the modern territories of Europe, Africa, and Asia. The obtained data will later on provide an opportunity to expand the understanding of the distribution of species—specifically for faunal research, as well as for biogeographic study.